SURFACE CURRENT STUDY USING LARGE PARTICLE IMAGE VELOCIMETRY METHOD IN ENDER ESTUARI, CIREBON REGENCY - Ramadhan Aqdam P, Muhammad
The Large-Scale Particle Image Velocimetry (LSPIV) method is an image-based technique that uses a non-intrusive approach or avoids direct physical contact with the water being studied to measure the velocity of water flow. The results of LSPIV are the speed and direction of the water surface being measured. In this study, surface velocity was measured in the estuary and river of Ender, Cirebon Regency using an unmanned aerial vehicle (UAV). The data was estimated using pyOpenRiverCam and compared to direct measurements using a current meter. The results of the LSPIV method are strongly influenced by the data acquisition process and the flow estimation process using pyOpenRiverCam. During data acquisition, factors such as lighting, seeding flow, video recording angle, and surrounding water conditions exist. In the flow estimation stage using pyOpenRiverCam, there are camera configuration, pre-processing, flow estimation using cross-correlation, and result visualization stages. From the measurement experiments, it was found that the LSPIV method is quite effective in estimating surface flow velocity, with a correlation (r) value of 0.82 for magnitude and 0.98 for flow direction, and an average MAPE (Mean Absolute Percentage Error) value of 15.146% for the measurements. In estimating flow direction using the LSPIV method, an average MAPE value of 12.851% was obtained.